The Aeneid of Virgil - Virgil. 4 0 16; Humphries, Rolfe; 5 (New York, Scribner, 1951)
Virgil's epic poem in verse translation describing the fall of Troy.
Young Adult;Young Adult
Keywords: 2 -- 0; 6; Translations into English. -- Epic poetry, Latin;Aeneas (Legendary character);Legends;Latin poetry. -- Rome -- Poetry.;Poetry.; 20; 2